Performance of Lightweight Concrete Beams Strengthened With GFRP (Port Said Engineering Research Journal, 2013)
This paper presents an investigation to improve the flexural behavior of reinforced lightweight concrete beams madeof light-weight expanded clay aggregate (LECA) as 50% replacement (by volume) to the normal -weight aggregates andaddition of foaming agent as percentage of weight of cement. A series of 44 lightweight reinforced concrete(LWRC) beams of 700 mm length and a rectangular cross section of 100x100 mm were cast, strengthened and thentested under three-points bending test to study the effectiveness of using externally applied glass fiber-reinforcedpolymer (GFRP) composites as a method of increasing the flexural strength of under-reinforced LWRC beams. Thevariables considered for this study was four concrete mixes and the number of GFRP layers with and without sulfateattack. The behavior of the tested beams was analyzed in terms of mode of failure load , ultimate carrying load, ultimatedeflection, and toughness . Despite the experimental results illus trated that the beams strengthened with GFRP laminatesexhibited better performance. Also the results show that the use of GFRP as an external reinforcement to strengthen orrepair concrete structural members (pre-loaded) is more effective